A VECM Study on Impact of Electricity Consumption in ASEAN - Susilowati, Indah; Sawo, Tirsa Erfani Pujiastuti; Himma, Nurrosyida Latifa; Sholikhah, Anna Uswatun (Universitas Negeri Semarang, 2025)
The objective of this study is to identify the long-term and short-term relationships between electricity consumption and employment, human welfare, and information and communication technology. The study uses panel data from ASEAN countries, covering 2015 to 2022. The sample consists of 8 countries with complete data for each variable within the specified period. Based on the results of testing using the Vector Error Correction Model, in the long term, electricity consumption has a significant positive relationship with employment and human welfare, which is proxied by the Human Development Index and Happiness Index. On the other hand, the relationship between electricity consumption and information and communication technology (ICT), proxied by the number of mobile cellular subscriptions, shows a significant negative result. In the short term, electricity consumption does not affect employment, human welfare, or information and communication technology. These results indicate that electricity consumption does not directly impact the improvement of human welfare but influences income levels directly through increased production processes and consumption of goods and services.